Simultaneous determination of l‐tetrahydropalmatine and its active metabolites in rat plasma by a sensitive ultra‐high‐performance liquid chromatography with tandem mass spectrometry method and its application in a pharmacokinetic study. (16th January 2017) - Wang, Weihui; Liu, Jing; Zhao, Xiaoning; Peng, Yan; Wang, Nannan; Lee, David Y.W.; Dai, Ronghua
Abstract: A sensitive and reliable ultra‐high‐performance liquid chromatography with tandem mass spectrometry (UHPLC–MS/MS) method was developed and validated for simultaneous determination ofl ‐tetrahydropalmatine (l ‐THP) and its active metabolitesl ‐isocorypalmine (l ‐ICP) andL ‐corydalmine (l ‐CD) in rat plasma. The analytes were extracted by liquid–liquid extraction and separated on a Bonshell ASB C18 column (2.1 × 100 mm; 2.7 μm; Agela) using acetonitrile–formic acid aqueous as mobile phase at a flow rate of 0.2 mL/min in gradient mode. The method was validated over the concentration range of 4.00–2500 ng/mL forl ‐THP, 0.400–250 ng/mL forl ‐ICP and 1.00–625 ng/mL forl ‐CD. Intra‐ and inter‐day accuracy and precision were within the acceptable limits of <15% at all concentrations. Correlation coefficients ( r ) for the calibration curves were >0.99 for all analytes. The quantitative method was successfully applied for simultaneous determination ofl ‐THP and its active metabolites in a pharmacokinetic study after oral administration withl ‐THP at a dose of 15 mg/kg to rats.